Hospitalized children with SARS-CoV-2 infection and MIS-C in Jamaica: A dive into the first 15 months of the novel pandemic - Crista-Lee Shahine Berry; Roxanne Helene Melbourne-Chambers; Roxanne Helene Melbourne-Chambers; Abigail Natalie Harrison; Abigail Natalie Harrison; Joshua James Anzinger; Joshua James Anzinger; Kelly-Ann Maxorinthia; Varough Mohamed Deyde; Celia Dana Claire Christie; Celia Dana Claire Christie (Frontiers Media S.A., 2022)
ObjectivesCOVID-19 in children was initially mild until the emergence of Multisystem Inflammatory Syndrome in Children (MIS-C). We describe pediatric COVID-19 in a developing country within the Caribbean.MethodsJamaican children who were hospitalized with SARS-CoV-2 infection, in one Caribbean regional academic referral center from April 2020 through June 2021 were included. Prospective surveillance and pediatric infectious disease consultations were performed using the CDC's MIS-C case definition. Data were extracted from patients' hospital charts using WHO's reporting form, entered into the RedCap database, and SPSS 28 was used for analysis. MIS-C and non-MIS-C patients were compared using independent sample t-tests for continuous variables and Fisher's exact test for categorical variables, p values < 0.05 were statistically significant.ResultsSeventy-nine children with COVID-19 with/without MIS-C presented to UHWI. Thirty-eight (48%) were mild ambulatory cases. Hospitalizations occurred in 41 (52%) children, with median age of 10 12 years. SARS-CoV-2 RT-PCR positivity was present in 26 (63%), Immunoglobulin M, or Immunoglobulin G (IgM/IgG) positivity in 8 (20%), with community exposures in 7 (17%). Eighteen (44%) MIS-C positive patients were significantly more likely than 23 MIS-C negative patients (56%) to present with fever (94% vs. 30%; p < 0.001), fatigue/lethargy (41% vs. 4%; p = 0.006), lymphadenopathy (33% vs. 0%; p = 0.003), elevated neutrophils (100% vs. 87%; p = 0.024), and ESR (78% vs. 9%; p = 0.002). Involvement of > two organ systems occurred more frequently in MIS-C positive cases (100% vs. 34%; p < 0.001), including gastrointestinal (72% vs. 17%; p < 0.001); vomiting/nausea (39% vs. 9%; p < 0.028); hematological/coagulopathic (67% vs. 4%; p < 0.001); dermatologic involvement (56% vs. 0%; p < 0.001); and mucositis (28% vs. 0%; p = 0.001). MIS-C patients had Kawasaki syndrome (44%), cardiac involvement (17%), and pleural effusions (17%). MIS-C patients had >4 abnormal inflammatory biomarkers including D-dimers, C-reactive protein, ESR, ferritin, troponins, lactate dehydrogenase, neutrophils, platelets, lymphocytes, and albumen (72%). MIS-C patients were treated with intravenous immune gamma globulin (78%), aspirin (68%), steroids (50%), and non-invasive ventilation (11%). None required inotropes/vasopressors. MIS-C negative patients received standard care. All recovered except one child who was receiving renal replacement therapy and developed myocardial complications.ConclusionsIn this first report of COVID-19 from the Caribbean, children and adolescents with and without MIS-C were not very severe. Critical care interventions were minimal and outcomes were excellent.